2016
DOI: 10.1002/jmri.25548
|View full text |Cite
|
Sign up to set email alerts
|

Small world properties changes in mild traumatic brain injury

Abstract: Purpose To investigate local and global efficiency changes characterized by small-world properties based on resting-state functional MRI, such as centrality and clustering coefficient, in mild traumatic brain injury (MTBI) patients; and to associate these findings with axonal injury as measured by diffusion tensor imaging (DTI) as well as with post-concussive symptom (PCS). Materials and Methods Thirty patients (mean age 35 ± 13 years) with clinically defined MTBI and 45 age-matched healthy controls (mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 45 publications
1
26
1
Order By: Relevance
“…To the best of our knowledge, there have been no studies comparing the change in the brain topological organization between participants who are cognitively impaired and nonimpaired where the participants in both groups are exposed to RHI. Nevertheless, when compared to healthy controls, Zhou () showed that graph‐theoretical measures in participants with mild TBI showed a decreased betweenness‐centrality but a higher clustering coefficient. However, no significant difference in any graph‐theoretical measures was observed in our cohort of impaired and nonimpaired professional fighters.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there have been no studies comparing the change in the brain topological organization between participants who are cognitively impaired and nonimpaired where the participants in both groups are exposed to RHI. Nevertheless, when compared to healthy controls, Zhou () showed that graph‐theoretical measures in participants with mild TBI showed a decreased betweenness‐centrality but a higher clustering coefficient. However, no significant difference in any graph‐theoretical measures was observed in our cohort of impaired and nonimpaired professional fighters.…”
Section: Discussionmentioning
confidence: 99%
“…The reported results of these invisible changes, however, are inconsistent in terms of functional connectivity. Some studies reported decreased global efficiency and increased modularity in patients with mild traumatic brain injury and posttraumatic stress disorder (4748). Conversely, several recent studies reported an increase in the resting functional connectivity after traumatic concussion relative to the controls (4950), which is in line with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Graph theory can help identify alterations in the global brain connectivity organization [64]. Previous studies have shown that TBI disrupts the optimal 'small-world' architecture of the network (as often observed in the healthy population), affecting the optimal balance between local segregation within and global integration between specialized independent subnetworks [64]; [65]; [66]. We seek to evaluate how TBI impairs this optimal integration/segregation balance at baseline and during balance perturbation.…”
Section: Effect Of Tbi On Eeg Brain Connectivity and Graph Measuresmentioning
confidence: 99%